Implementasi Peraturan Walikota Medan Nomor 8 Tahun 2017 Tentang Pajak Restoran Di Kota Medan (Studi Kasus di Badan Pengelolah Pajak Dan Retribusi Daerah Kota Medan) - Reza Fahmi; Abdul Kadir; Beby Mashito Batu Bara (Jurnal Ilmu Pemerintahan, Administrasi Publik, dan Ilmu Komunikasi (JIPIKOM), 2019)
The purpose of this study was to determine the implementation of Medan Mayor Regulation No. 8 of 2017 Regarding Restaurant Taxes in Medan City. The study uses descriptive qualitative design, which is research that is limited to efforts to reveal a problem or condition or event as it is so that it is merely revealing facts (fact finding). The results of this study indicate that the implementation of Medan Mayor Regulation No. 8 of 2017 concerning Restaurant tax in Medan has an impact on adjusting the communication process between Medan City Tax and Retribution Management Agency officials and taxpayers. Implementation of Medan Mayor Regulation No. 8 of 2017 Regarding Restaurant Tax has no impact on the structure and disposition of taxpayers. While for the Medan City Regional Tax and Retribution Management Agency the structure and disposition have an impact on internal performance. Implementation of Medan Mayor Regulation No. 8 of 2017 is the most affected element. Implementation officers for the Medan mayor regulation require changes in attributes, logos, letter content formats, reporting forms and tax payments. Changes to these items require quite a long time due to the procurement of goods and services that have just been implemented by a unit outside the Medan City Regional Tax and Retribution Management Agency.